Peculiarities of Platform Firms’ Internationalization in the Context of Latest Theories of International Business and Strategic Management - Milena M. BALANOVA; Oleg V. BODIAGIN; Inga A. MEZINOVA (Communications of International Proceedings, 2021)
Analyzing the activities of firms in global markets, contemporary economic science is facing new challenges − the emergence of a new type of global companies, their mechanism of internationalization being incompatible the traditional theoretical models of international business − the internalization model and the model of gradual internationalization of international business. The paper explores the applicability of new interdisciplinary approaches to explaining the international expansion of platform companies with a special emphasis on resource-based approaches to determining the source of competitive advantages of new firms.
Keywords: Platform Firms; Internationalization; Theories of International Business; Dynamic Capabilities